MODERASI UKURAN PERUSAHAAN PADA PENGARUH PROFITABILITAS, LEVERAGE DAN CAPITAL INTENSITY TERHADAP PENGHINDARAN PAJAK - Tarigan, Ekavina Dustira; Sari , Diana (Politeknik Negeri Ambon, 2025)
Introduction: This study aims to examine the effect of profitability, leverage, and capital intensity on tax avoidance, as well as to analyze the role of firm size as a moderating variable. The research objects are mining sector companies listed on the Indonesia Stock Exchange (IDX) during the 2019–2022 period. Method: The study employs a quantitative approach using moderated regression analysis (MRA). Secondary data were obtained from the companies’ annual financial statements officially published on the IDX website. Results: The results show that leverage and capital intensity have a significant effect on tax avoidance, while profitability does not show a significant effect. Furthermore, firm size is proven to moderate the relationship between leverage and capital intensity on tax avoidance but does not moderate the influence of profitability. These findings provide implications for regulators and corporate management to consider firm size in designing strategies for tax compliance and supervision in the mining sector. Keywords: Tax Avoidance, Profitability, Leverage, Capital Intensity and Firm Size